On the Road: The Challenges and Benefits of Agency Research. Issue 7 (3rd October 2021) - Koetzle, Deborah; Ndrecka, Mirlinda; Johnson, Shelley
ABSTRACT: The importance of researcher-practitioner collaborations is at the core of Edward J. Latessa's work. He has been at the forefront of this domain by creating and disseminating evidence-based tools and practices throughout his career. His work with agencies has undoubtedly changed the face of correctional practices in America and throughout the world. The current essay outlines the work that Ed did to propagate the "what works" movement by doing translational criminology work, and the lessons learned from him on the road.